Spice model design for carbon nanotube field effect transistor (CNTFET) - Farhana, Soheli; Alam, A. H. M. Zahirul; Khan, Sheroz (2014)
In this paper, the design of SPICE circuit model has been discussed for Carbon Nanotube Field Effect Transistor (CNTFET) and predict device high frequency performance. An enhancement mode SPICE circuit model for nanotube transistor has been developed. A new CNTFET circuit can be developed by using this SPICE model. It can be also used to examine the performance benefits of the newly built transistor. The carbon nanotube field effect transistor SPICE model has been analyzed on the high frequency properties including the persuade of ballistic transport, kinetic inductance and quantum capacitance. The model enables device design and performance optimization for the future generation nano-electronics device modeling.